Self-perception of friendship style: Young adults with and without autism spectrum disorder. (June 2019) - Finke, Erinn H; McCarthy, Jillian H; Sarver, Natalie A
Background: It has been reported that people on the autism spectrum have difficulty making and maintaining friendships. Congruence of perspective on friendships and friendship practices may affect the frequency and intensity of friendships, but this is not well understood. Aims: The aims of the current project were to identify the similarities and differences in the broad perspectives and friendship practices of young adults with and without autism. Method and procedures: Young adults with and without autism between the ages of 18 and 24 years completed an online survey to determine the friendship preferences that most define the perspectives of young adults with autism. Outcomes and results: The results identified primarily differences in the broad perspectives and friendship practices of young adults with and without autism spectrum disorder, which may provide a context for understanding the values and priorities that need to be considered as two people (whether they have an autism spectrum disorder diagnosis or not) embark on a new potential friendship, and may help people with autism (as well as clinicians, educators, and caregivers) understand why some friendships flounder and others are established and maintained with relative ease.